Numerical analysis of pulsing regimes near static borders of optically injected semiconductor lasers - Rodriguez, Sergio; Campuzano, Gabriel; Aldaya, Ivan [UNESP]; Castañón, Gerardo (Optica Publishing Group, 2022)
It is well known that semiconductor lasers under optical injection present rich, dynamic behavior. In this paper, we focus on pulsing regimes, which can be either exploited in a broad variety of applications or lead to undesired instabilities. In particular, we develop a multi-metric method to automatically identify pulsing regimes in the parameter space.We apply this method to extensive numerical simulations to show that these regimes occur in the vicinity of the static synchronization boundary. Furthermore, analyzing these pulsing regimes, we identify pulsations with repetition rates ranging from several megahertz up to more than 1 GHz. Finally, we analyze the effect of the linewidth enhancement factor and the slave-laser bias current, revealing that a linewidth enhancement factor of 3 and a higher bias current lead to broader regions of pulsation regimes.